P–374 Investigating causality of risk factors for miscarriage – a Mendelian randomization analysis. (6th August 2021) - Painter, J; Laisk, T; Lindgren, C; Medland, S
Abstract: Study question: Do modifiable risk factors such as smoking, alcohol or coffee consumption, and adiposity causally increase the risk of sporadic or recurrent miscarriage? Summary answer: We found evidence for a causal relationship between smoking initiation and sporadic miscarriage, but not for any other risk factor tested. What is known already: Miscarriage is estimated to end between 10–25% of clinically confirmed pregnancies, and many observational studies have suggested numerous lifestyle factors, such as coffee and alcohol consumption, smoking and increased adiposity, may increase miscarriage risk. However, results are not always consistent across studies, and definitive causal relationships between various risk factors and miscarriage have not yet been demonstrated. Mendelian randomization utilizes genetic variants significantly associated with heritable risk factors (i.e. at P-values <5x10–8 in large genome-wide association studies) as instrumental variables to investigate causality of risk factors in population health outcomes. Study design, size, duration: We conducted two-sample Mendelian randomization analyses to investigate causality of smoking (initiation and quantity), alcohol and coffee consumption (quantity), and adiposity (body mass index and waist-hip ratio) in sporadic and recurrent miscarriage. Data included in this study were taken from previously published summary genetic association statistics (betas, standard errors and P-values) from large-scale genome-wide association studies (GWAS) for each risk factor, and from our recently published GWAS of sporadic and recurrent miscarriage. Participants/materials, setting, methods: Instrumental variables were constructed using 5–306 genetic variants significantly associated with the listed risk factors in published GWAS (minimum N = 178, 000 individuals). Two instrumental variables were constructed per risk factor using data from different GWAS. Associations of the instrumental variables with miscarriage were investigated using summary association data from women of European ancestry included in our miscarriage GWAS, including 49, 996 sporadic miscarriage cases and 174, 109 female controls, and 750 recurrent miscarriage cases and 150, 215 female controls. Main results and the role of chance: We found a significant association between sporadic miscarriage and the instrumental variables for two smoking measures: smoking initiation (inverse variance weighted Odds Ratio = 1.17, 95% confidence intervals = 1.10–1.24, P = 2.7 x 10–07) and lifetime smoking (inverse variance weighted Odds Ratio = 1.22, 95% confidence intervals 1.11–1.35, P = 4.2x10–5). No other risk factors (smoking quantity, coffee or alcohol consumption, or BMI or waist-hip ratio) were associated with either sporadic or recurrent miscarriage. A priori power calculations considering the amount of phenotypic variance in each risk factor explained by the associated SNPs suggested our analysis to have at least 75% power to detect an association with Odds Ratio of 1.2 with sporadic miscarriage for analyses of body mass index, waist hip ratio and smoking initiation, quantity and the lifetime smoking measure, but that the alcohol and coffee consumption analyses were underpowered (4.9% and 48%, respectively). All analyses were underpowered for recurrent miscarriage given the small case sample size (N = 750). Limitations, reasons for caution: While data utilised here come from large-scale GWAS including 1000s of individuals, genetic variants significantly associated with each risk factor currently explain small percentages (0.02–6%) of the variance in each trait. Larger GWAS for specific risk factors, and for sporadic and recurrent miscarriage, are required to clarify some published associations. Wider implications of the findings: We find no evidence of a causal link between adiposity and miscarriage, indicating that observational findings of increased miscarriage risk with increasing body mass index require further explanation. Significant associations between measures of ever-smoking and sporadic miscarriage highlights that no amount of smoking is safe in regards to miscarriage risk. Trial registration number: Not applicable